Под призрачным прикрытием: [роман] / Сергей Самаров - Самаров Сергей Васильевич (Спецназ ГРУ, 2015)
Экземпляры: ЦБ (20221121) / Инвентарный номер: 55767 / Цена: 200.00 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: С 17 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44